Shatterglass - Pierce, Tamora (New York : Scholastic, 2003)
Tris and her mage-student, a young man whose glassmaking magic has been amplified and mixed with lightning, team up to track a killer who may be nearer than they suspect.
Keywords: Magic -- Juvenile fiction; Magic -- Fiction; Fantasy; Fantasy fiction